Kearifan lokal dalam novel Seulusoh karya D. Kemalawat - Wildan, Wildan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This study aims to identify the local wisdom reflected through the life experiences of a socio-cultural system in Seulusoh, a novel by D. Kemalawati. The method used in this study is a qualitative analytic approach applying content analysis and in-depth interviews. The results indicate that the local wisdom articulated in the novel includes the celebration of holy days such as Ramadan fasting, meugang, and Eid al-Fitr; the inheritance of values from the older generation to the younger generation, from grandparents to grandchildren, and from parents or teachers to children; skills in making and serving traditional foods such as ie bu peudah and timphan; as well as beliefs and myths. This local wisdom is implied as a means of preserving traditional values, enhancing the ability to read signs of nature, and maintaining family pride and tradition.